The role of civil society organisations in the implementation of youth policy in South Africa - Mudimu, Rufaro (My University, 2017)
Since the development of the World Programme of Action for Youth to the year 2000 and Beyond (United Nations, 2010), youth and the associated development issues that affect and are effected by them have risen to prominence. In South Africa, 66% of the population are under the age of 34 (the cut-off age for youth), and 36% are between the ages of 15-34 years old, and there is a general perception and concern that current youth policy is failing (Maupa, 2013; NUMSA Bulletin basic, 2014; Setiloane, 2014; South African Broadcasting Corporation, 2011). From anecdotal evidence, personal experience as a youth development practitioner and brief analysis of the literature, there appears to be limited strategic and deliberate engagement of youth and youth-oriented CSOs in the youth policy formulation and implementation process. The purpose of this research is to explore the perceived and real barriers to the involvement of CSOs in youth policy implementation in South Africa. A policy implementation research lens is applied in a broad analysis of the National Youth Policy 2015-2020 and its implementation, exploration of the involvement of CSOs in the policy process and assessment of perceived and real barriers of involvement for CSOs. The research study was an attempt to address the identified knowledge gap regarding youth policy implementation in the South African context (O’Toole, 2000; Saetren, 2005) and the potential role of civil society in that policy process. To some extent, the data, findings and analysis discussed addressed the knowledge gap in that they described how the youth policy is being implemented; identified the key role players in the implementation, and the ways in which civil society may be involved. The research findings and analysis answered the research questions, revealing the barriers to civil society, the nature of youth and CSO engagement by government. In conclusion, this study sheds light on the policy implementation, youth engagement, and civil society involvement, providing clarity and recommendations that may enhance youth participation and civil society and state partnership in policy implementation.
Research Report submitted to the University of the Witwatersrand, School of Governance in fulfillment of the requirements for the degree of Masters in Management in Public and Development Management (50% Research)
Keywords: Youth--Government policy--South Africa; Non-governmental organizations--South Africa